Efeitos de frustração geométrica em antiferromagnetos desordenados com clusters - Schmidt, Mateus (2019)
In magnetic systems, frustration - which refers to the inhability to satisfy all the interactios simultaneously - has ravealed a rich phenomenology. In particular, disorder and geometrical features are possible sources of frustration. Systems that combine these two sources generally give rise to a number of challenging problems. In the present work, we approach the interplay between geometrical frustration (GF) and bond disorder, focusing in the rich phenomenology underlying the cluster spin glass (CSG) phase stabilization. In order to deal with this problem we considered the van Hemmen and the Sherrington-Kirkpatrick cluster models, as well as cluster mean-field methods. Our studies focused on the J1-J2 square, the antiferromagnetic kagome and the checkerboard Ising lattices with intercluster disorder. In the square and kagome lattices, we studied the CSG onset at low levels of disorder in geometrically frustrated systems, which is a problem with great experimental motivation. Our results indicate that the increase in frustration (by tuning J2=J1) reduces the minimum amount of disorder needed to stabilize the CSG in the square lattice. Moreover, for the kagome lattice, we found that an infinitesimal disorder leads to a CSG ground-state. This result can be compared to the experimental findings for the Co3Mg(OH)6Cl2 compound, that is pointed out as an experimental realization of the Ising kagome antiferromagnet. Moreover, we investigate the effects of GF on the onset of reentrant transitions. In this study, we considered a model with disorder between clusters in the presence of an external longitudinal magnetic field. Our results indicate that cluster magnets are prototypes for the observation of inverse freezing. Besides, at weak disorders, we observed the onset of field-induced CSG phases, indicating that cluster antiferromagnets are also candidates for field-induced glassy phases.